Modulation of Emotion Perception via Amygdala Stimulation in Humans - Bujarski, Krzysztof A.; Song, Yinchen; Xie, Tiankang; Leeds, Zachary; Kolankiewicz, Sophia I.; Wozniak, Gabriella H.; Guillory, Sean; Aronson, Joshua P.; Chang, Luke; Jobst, Barbara C. (Frontiers in Neuroscience, 2022)
Background: Multiple lines of evidence show that the human amygdala is part of a neural network important for perception of emotion from environmental stimuli, including for processing of intrinsic attractiveness/”goodness” or averseness/”badness”, i.e. affective valence. Objective/Hypothesis: With this in mind, we investigated the effect of electrical brain stimulation of the human amygdala on perception of affective valence of images taken from the International Affective Picture Set (IAPS). Methods: Using intracranial electrodes in patients with epilepsy, we first obtained event-related potentials (ERPs) in 8 patients as they viewed IAPS images of varying affective valence. Next, in a further cohort of 10 patients (5 female and 5 male), we measured the effect of 50 Hz electrical stimulation of the left amygdala on perception of affective valence from IAPS images. Results: We recorded distinct ERPs from the left amygdala and found significant differences in the responses between positively and negatively valenced stimuli (p = 0.002), and between neutral and negatively valenced stimuli (p=0.017) 300-500 milliseconds after stimulus onset. Next, we found that amygdala stimulation did not significantly affect how patients perceived valence for neutral images (p=0.58), whereas stimulation induced patients to report both positively (p=0.05) and negatively (<0.01) valenced images as more neutral. Conclusion: These results render further evidence that the left amygdala participates in a neural network for perception of emotion from environmental stimuli. Furthermore, these findings support the idea that electrical stimulation disrupts this network and leads to partial disruption of perception of emotion. Harnessing this effect may have clinical implications in treatment of certain neuropsychiatric disorders using deep brain stimulation (DBS) and neuromodulation.